Enzyme response type visible light nano-silver synergistic antibacterial film and preparation method thereof
Through the enzyme-responsive visible nano-silver synergistic antibacterial membrane, the enzymatic activation mechanism of HCNS-Ag-SH-HA composite material is used to solve the problem of uncontrolled release of silver ions in silver-based antibacterial membrane materials, and the on-demand antibacterial and environmentally friendly are achieved efficient sterilization effect.
Patent Information
- Application Number
- CN202411355701.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing silver-based antibacterial membrane materials have the problem of uncontrollable continuous release of silver ions, which leads to toxic side effects and waste of resources on the water environment. At the same time, the antibacterial characteristics are greatly reduced after the silver ions are completely released.
Using an enzyme-responsive visible nanosilver synergistic antibacterial membrane, it was prepared from HCNS-Ag-SH-HA composite material. It coated carbon nitride hollow spheres with thiolated hyaluronic acid to form an enzymatically exposed antibacterial component to slow down The release and consumption of Ag+ achieves antibacterial on demand.
It effectively avoids the uncontrollable continuous release of Ag+ to the environment and waste of resources, extends the service life of the membrane material, and improves the antibacterial effect under visible light.
Smart Images

Figure CN119242044A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane materials, and in particular to an enzyme-responsive visible light nano-silver synergistic antibacterial membrane and a preparation method thereof. Background Art
[0002] Membrane separation technology is widely used in water treatment, food processing, pharmaceutical production and other fields due to its excellent filtration and retention performance. However, "membrane pollution" is still the most serious challenge it faces in practical applications. According to the type of pollutants, "membrane pollution" can be divided into organic pollution, inorganic pollution and biological pollution. Among them, biological pollution caused by the attachment, growth and reproduction of microbial cells or flocs on the membrane surface and in the membrane pores is considered to be the most harmful membrane pollution.
[0003] Carbon nitride has an appropriate medium-wide band gap and can effectively absorb visible light, so it is widely used in the fields of photocatalytic degradation of organic pollutants and photolysis of water to produce hydrogen. In addition, studies have shown that visible light irradiation can cause g-C3N4 to produce reactive oxygen species (ROS) to kill Escherichia coli K-12 in water.
[0004] As an excellent broad-spectrum antibacterial agent, nanosilver has been widely used in the preparation of anti-pollution membrane materials. The existing technology introduces silver-based antibacterial agents into membrane materials by means of blending, grafting, loading, etc. Nanosilver can release silver ions in aqueous media, which have a toxic effect on cell membranes and enzyme systems, leading to enzyme inactivation and the generation of reactive oxygen species (ROS) to achieve antibacterial effects. In addition, the physical contact between nanoparticles and microorganisms can also change the properties of cell membranes, destroy the structure of microorganisms, and reduce the adhesion, growth and biofilm formation of bacteria on the membrane surface and in the pores, so that the nanocomposite membrane material has good anti-biological pollution performance, thereby extending the service life of the membrane material.
[0005] However, the current silver-based antibacterial film materials all have the problem of "uncontrollable and continuous release of silver ions". Their "permanent release state" is bound to cause certain toxic side effects and waste of resources to organisms in the aquatic environment. When the silver ions are completely released, their antibacterial properties will also be greatly reduced. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides an enzyme-responsive visible light nanosilver synergistic antibacterial film and a preparation method thereof, which can realize the synergistic antibacterial effect of photocatalysis and metallic silver under visible light. By exposing the antibacterial components through enzyme catalysis, -SH binding can more effectively slow down the Ag + Release and consumption, achieve on-demand antibacterial, avoid Ag + Uncontrolled continuous release causes toxic side effects to the environment and waste of resources.
[0007] The technical solution adopted by the present invention to solve its technical problems is: an enzyme-responsive visible light nanosilver synergistic antibacterial film, which is prepared by blending a HCNS-Ag-SH-HA composite material into a membrane material; wherein the HCNS-Ag-SH-HA composite material is prepared by loading silver ions on hollow carbon nitride spheres and then coating them with a thiolated hyaluronic acid compound; in the antibacterial film, the mass proportion of the HCNS-Ag-SH-HA composite material is 0.1-3%.
[0008] Furthermore, the membrane material is one or a combination of two or more of polyethersulfone, polysulfone, polyvinylidene fluoride, cellulose acetate, polyamide, and chitosan.
[0009] A method for preparing an enzyme-responsive visible light nanosilver synergistic antibacterial film is specifically carried out according to the following steps:
[0010] A1. Add the HCNS-Ag-SH-HA composite material to an organic solvent and stir until it is evenly dispersed to obtain a mixed solution;
[0011] A2, adding membrane material to the mixed solution of step A1, heating to dissolve at 50-80°C, stirring for 10-20h, and then standing for 20-30h to remove bubbles to obtain a casting solution;
[0012] A3, forming an antibacterial film using the casting liquid obtained in step A2.
[0013] Furthermore, in step A3, the method for forming the antibacterial film with the casting liquid is: pour the casting liquid of step A2 on the non-woven fabric, spread it evenly, and then immerse the entire non-woven fabric in a gel bath to solidify it to form a film of uniform thickness, and continue immersing it for 24 hours to complete the phase conversion.
[0014] Furthermore, in the method for forming an antibacterial film with a casting liquid, the gel bath is pure water, a propanol solution with a volume concentration of 5-10%, or an ethanol solution with a volume concentration of 2-10%.
[0015] Further, the HCNS-Ag-SH-HA composite material is prepared according to the following steps:
[0016] B1, dispersing hollow carbon nitride spheres in water, adding AgNO3 solution thereto, and adjusting the pH of the system to 4-6 with nitric acid; stirring for 10-20 hours in the dark, and then separating the solid, washing, to obtain hollow carbon nitride spheres loaded with silver ions; wherein the mass ratio of the hollow carbon nitride spheres to AgNO3 is 1:(0.34-0.85);
[0017] B2. The silver ion-loaded carbon nitride hollow spheres prepared in step B1 are dispersed in water, and a thiolated hyaluronic acid compound is added thereto. The mixture is stirred for 8-12 hours at room temperature in the dark, and then the solid is separated. After dialysis and freeze-drying, a HCNS-Ag-SH-HA composite material is obtained. The mass ratio of the silver ion-loaded carbon nitride hollow spheres to the thiolated hyaluronic acid compound is 1:(2-5).
[0018] Furthermore, the dispersion in step B1 is ultrasonic dispersion.
[0019] Furthermore, the hollow carbon nitride spheres are prepared according to the following steps:
[0020] C1. Preparation of silica template with core / shell structure;
[0021] C2, taking the silica template from step C1, acidifying it with HCl solution, separating the solid, and drying it;
[0022] C3, mixing the solid of step C2 with cyanamide, ultrasonically treating at 65° C. for 4 h, and then stirring at 65° C. for 10-20 h; separating the solid, and then calcining at 550° C. for 4 h in a nitrogen atmosphere, cooling, treating the carbon nitride spheres with ammonium bifluoride solution for 12 h, separating the solid, washing, and freeze-drying to obtain hollow carbon nitride spheres; wherein the mass ratio of the silica template to the cyanamide is 1:(3-7).
[0023] Furthermore, the core / shell structured silica template is prepared according to the following steps:
[0024] D1. Take ethanol, ultrapure water and ammonia water and mix them evenly to obtain a mixed solution; wherein the mass percentage of ammonia water is 25%, and the volume ratio of ethanol, ultrapure water and ammonia water is (12-18):(2-4):1;
[0025] D2, taking the mixed solution of step D1, adding tetraethyl orthosilicate thereto, stirring evenly, and then standing for 2 hours to obtain a mixed solution containing silica core nanoparticles, wherein the volume ratio of ammonia water to tetraethyl orthosilicate added in step D2 is (1.5-1.8):1;
[0026] D3, to the mixed solution obtained in step D2, add tetraethyl orthosilicate and octadecyltrimethylsiloxane, stir evenly, then let stand for 10 hours, separate the mixture, and dry; then calcine at 550° C. for 6 hours under air atmosphere to obtain a silica template with a core / shell structure; wherein the volume ratio of tetraethyl orthosilicate added in step D3 to the mixed solution obtained in D2 is (0.025-0.035):1; the mass ratio of tetraethyl orthosilicate added in step D3 to octadecyltrimethylsiloxane is 1:(0.3-0.4).
[0027] Advantages of the present invention: The enzyme-responsive visible light nanosilver synergistic antibacterial film and its preparation method can realize the synergistic antibacterial effect of photocatalysis and metallic silver under visible light. The antibacterial components are exposed by enzyme catalysis, and the combination of thiol groups can more effectively slow down the Ag + Release and consumption, achieve on-demand antibacterial, avoid Ag + Uncontrolled continuous release causes toxic side effects to the environment and waste of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The surface contact angle diagrams of the antibacterial films of HCNS-Ag-SH-HA with different addition amounts in Examples 1 to 5;
[0029] Figure 2 Ag content of the HCNS-Ag-SH-HA composite material of the embodiment and the HCNS-Ag-HA composite material of the comparative example within 60 hours under different conditions + Comparison chart of release behavior;
[0030] Figure 3 This is a comparison chart of the bactericidal effect of the antibacterial film of the embodiment on Streptococcus pneumoniae under no light conditions and under light conditions. DETAILED DESCRIPTION
[0031] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The embodiments are only used to explain the present invention and do not limit the protection scope of the present invention.
[0032] Embodiment 1
[0033] Preparation of core / shell structured silica templates:
[0034] Ethanol (150 mL), ultrapure water (30 mL) and ammonia water (25 wt%, 10 mL) were placed in a flask and mixed for 30 minutes, and tetraethyl orthosilicate TEOS (5 mL) was added and stirred. After standing for 2 hours, a silica core nanoparticle solution was obtained. Then, tetraethyl orthosilicate TEOS (6 mL) and octadecyl trimethylsiloxane C18-TMOS (2.0 g) were added to the silica core nanoparticle solution and stirred continuously; after standing at room temperature for 10 hours, the solid was separated and dried at 80°C for 24 hours. Finally, the core / shell structured silica template was obtained by calcining at 550°C for 6 hours in an air atmosphere.
[0035] Preparation of hollow carbon nitride spheres (HCNS):
[0036] Take 1.6g of the core / shell structured silica template obtained above and acidify it with HCl solution (1M, 5mL) at 70°C. Centrifuge to obtain a solid, dry it, then mix cyanamide (8g) with the obtained silica template, ultrasonically treat it at 65°C for 5h, and stir the mixture at 65°C overnight. After centrifugation, cyanamide-loaded silica is obtained. Subsequently, after calcining at 550°C for 4 hours in a N2 atmosphere, cool it to room temperature, and then treat the carbon nitride ball with ammonium bifluoride solution (0.5mol / L) for 12h. Finally, separate the solid, wash it, and freeze-dry it to obtain yellow HCNS.
[0037] Silver ion loaded hollow carbon nitride spheres (HCNS-Ag + ) Preparation:
[0038] Take 1g of the above HCNS, ultrasonically disperse it in ultrapure water, add 35mL of 0.1mol / L silver nitrate solution, adjust the pH of the system to 5 with nitric acid, stir overnight in the dark, and wash to obtain HCNS-Ag + .
[0039] Among them, ultrasound can greatly improve the dispersion of HCNS powder in the liquid phase, fully expose the active sites in its core-shell structure, and be more conducive to Ag + The combination and loading of Ag, dark conditions and slightly acidic environment can prevent + is restored.
[0040] Preparation of HCNS-Ag-SH-HA composites:
[0041] 60 mL of 0.1 mg / mL thiolated hyaluronic acid HA-SH and 1 mL of 2 mg / mL HCNS-Ag + The mixture was mixed and stirred at room temperature in the dark for 8-12 hours to form a HCNS-Ag-SH-HA composite material. The product was dialyzed and freeze-dried and then ground into powder.
[0042] Preparation of antibacterial film:
[0043] Take 0.1 g of the aforementioned HCNS-Ag-SH-HA composite material, add it to the organic solvent N,N-dimethylacetamide (DMAc) and stir to make it evenly dispersed, then add 16 g of polyethersulfone (PES), place it in an oven and heat it at 60°C to dissolve, and then place it on a magnetic stirrer and stir overnight; take it out the next day and let it stand at room temperature for 24 hours to remove tiny bubbles in the casting liquid, so that the solvent diffuses into the water and the pore structure of the polymer solidified into the film is more perfect, and the generation of pores is reduced; after the casting liquid is prepared, pour the casting liquid on the non-woven fabric, scrape it evenly with a scraper, and quickly immerse the glass plate covered with the non-woven fabric in a gel bath such as pure water to solidify it to form an asymmetric membrane of uniform thickness, and continue to immerse it for more than 24 hours to complete the phase conversion.
[0044] Among them, adjusting the standing time and the composition of the gel bath can effectively regulate the pore size and structure of the antibacterial membrane.
[0045] In this embodiment, by controlling the addition amount of the HCNS-Ag-SH-HA composite material and the addition amount of the polyethersulfone, the mass proportion of HCNS-Ag-SH-HA in the final antibacterial film is 0.1%.
[0046] Embodiment 2
[0047] In this embodiment, by controlling the addition amount of the HCNS-Ag-SH-HA composite material and the addition amount of the polyethersulfone, the mass proportion of HCNS-Ag-SH-HA in the final antibacterial film is 0.5%. The rest is the same as in the first embodiment.
[0048] Embodiment 3
[0049] In this embodiment, by controlling the addition amount of the HCNS-Ag-SH-HA composite material and the addition amount of the polyethersulfone, the mass proportion of HCNS-Ag-SH-HA in the final antibacterial film is 1%. Others are the same as in the first embodiment.
[0050] Embodiment 4
[0051] In this embodiment, by controlling the addition amount of the HCNS-Ag-SH-HA composite material and the addition amount of the polyethersulfone, the mass proportion of HCNS-Ag-SH-HA in the final antibacterial film is 2%. The rest is the same as in the first embodiment.
[0052] Embodiment 5
[0053] In this embodiment, by controlling the addition amount of the HCNS-Ag-SH-HA composite material and the addition amount of the polyethersulfone, the mass proportion of HCNS-Ag-SH-HA in the final antibacterial film is 3%. The rest is the same as in the first embodiment.
[0054] Comparative Example 1
[0055] In this comparative example, by controlling the addition amount of the HCNS-Ag-SH-HA composite material and the addition amount of the polyethersulfone, the mass proportion of HCNS-Ag-SH-HA in the final antibacterial film is 0.05%. The rest is the same as in Example 1.
[0056] Comparative Example 2
[0057] In this comparative example, by controlling the addition amount of the HCNS-Ag-SH-HA composite material and the addition amount of the polyethersulfone, the mass proportion of HCNS-Ag-SH-HA in the final antibacterial film is 4%. The rest is the same as in Example 1.
[0058] Comparative Example 3
[0059] In this comparative example, in the preparation of the HCNS-Ag-SH-HA composite material, 60 mL of 0.1 mg / mL thiolated hyaluronic acid HA-SH in Example 1 was replaced with 60 mL of 0.1 mg / mL hyaluronic acid HA to prepare a HCNS-Ag-HA composite material.
[0060] The hydrophilicity test of the antibacterial films of Examples 1 to 5 was performed; the test results are as follows: Figure 1 As shown, the contact angle of the antibacterial film of Example 1 is 80°; the contact angle of the antibacterial film of Example 2 is 72°; the contact angle of the antibacterial film of Example 3 is 60°; the contact angle of the antibacterial film of Example 4 is 52°; and the contact angle of the antibacterial film of Example 5 is 50°. With the increase of the amount of HCNS-Ag-SH-HA composite material added, the hydrophilicity of the antibacterial film can be improved, because the thiolated hyaluronic acid can increase the hydrophilicity of the film surface. The improvement of hydrophilicity can effectively inhibit the adhesion of bacteria to the antibacterial film in the early stage.
[0061] The HCNS-Ag-SH-HA composite material prepared in Example 1 and the HCNS-Ag-HA composite material prepared in Comparative Example 3 were compared to Ag. + The release behavior was tested by the following method: three groups of aqueous dispersions of HCNS-Ag-SH-HA composite materials were prepared. Each dispersion was prepared by ultrasonically dispersing 0.1 g of HCNS-Ag-SH-HA composite materials in 200 mL of deionized water. Subsequently, no hyaluronidase was added to the first dispersion, hyaluronidase (0.1 mg / mL, 10 mL) inactivated by 100°C treatment was added to the second dispersion, and hyaluronidase (0.1 mg / mL, 10 mL) was added to the third dispersion. After all three groups were allowed to stand for 60 hours, the Ag released from the solution was tested by inductively coupled plasma mass spectrometry (ICP-MS). + concentration, and then calculate the Ag+ The release amount; the test results are as follows Figure 2 As shown, in the absence of hyaluronidase (no HAase), under the conditions of 60h, the Ag of the HCNS-Ag-SH-HA composite material of Example 1 + The release amount is 8%, and the Ag of the HCNS-Ag-HA composite material of comparative example 3 + The release amount was 11.1%; under the conditions of inactivated hyaluronidase (inactivated HAase) and 60h, the Ag of the HCNS-Ag-SH-HA composite material of Example 1 + The release amount is 8.6%, and the Ag of the HCNS-Ag-HA composite material of comparative example 3 + The release amount was 11.5%; in the presence of hyaluronidase (HAase) for 60 h, the Ag of the HCNS-Ag-SH-HA composite material of Example 1 + The release amount is 30.6%, and the Ag of the HCNS-Ag-HA composite material of comparative example 3 + The release amount was 59.4%. The results showed that in the presence of hyaluronidase, Ag + The release amount was significantly higher than that of Ag without hyaluronidase or inactivated hyaluronidase + Release amount; and at the same time (60h), the Ag of the HCNS-Ag-SH-HA composite material of this embodiment + The release rate is significantly higher than that of the HCNS-Ag-HA composite material in comparative example 3. + The release rate is slow; this is because HA can be coated on HCNS-Ag through electrostatic interaction. + The outside forms an electrostatic barrier to effectively prevent Ag + The -SH group in HA-SH can react with Ag + Form a more stable structure SH-Ag, effectively slowing down Ag + When hyaluronidase is added, the hyaluronic acid layer will be destroyed, exposing the effective antibacterial component Ag, and continuously releasing Ag. + Released into the aqueous solution. Due to the stronger bonding force between silver and -SH in the HCNS-Ag-SH-HA composite material, Ag is released into the aqueous environment. + The rate is slower.
[0062] The bactericidal effect of the antibacterial film prepared in Example 2 was tested. Testing method: Streptococcus pneumoniae was dispersed in a PBS buffer solution with a pH of 7.0 to prepare 10 8 CFU / mL bacterial suspension, added to an area of 10cm 2The film was used to provide a visible light source using a xenon lamp. Samples were taken at intervals and diluted to a certain multiple. The bacterial survival rate was calculated using the solid plate coating method. Figure 3 As shown, under the condition of no light and 24 hours, the bacterial survival rate was 25.7%; under the condition of light and 24 hours, the bacterial survival rate was 5.4%; in comparison, under the condition of light, the bacterial survival rate was lower, which further illustrates that under the condition of light, the synergistic antibacterial effect of the hollow carbon nitride spheres and silver ions in the antibacterial film is better.
[0063] For the antibacterial nanocomposite membrane materials of Examples 1 to 5 and Comparative Examples 1 and 2, the only difference is that the addition amount of the HCNS-Ag-SH-HA composite material is different. As the addition amount of the HCNS-Ag-SH-HA composite material increases, the content of the antibacterial component Ag in the antibacterial film also increases, and the antibacterial effect is also better, but it follows that when the addition amount of the HCNS-Ag-SH-HA composite material is too much (such as Comparative Example 2), the HCNS-Ag-SH-HA composite material is difficult to be evenly dispersed in DMAc, and it is easy to agglomerate on the surface of the composite membrane, and the viscosity of the casting liquid will be greatly increased, which is not conducive to the subsequent formation of well-developed finger-like pores in the composite membrane in the gel bath, and the flux of the composite membrane will be greatly reduced, that is, it will have a significant adverse effect on the filtration and interception performance of the nanocomposite membrane, and if the HCNS-Ag-SH-HA composite material is too low (such as Comparative Example 1), the antibacterial effect is not obvious. Therefore, selecting an addition amount of 0.1%-3% of the HCNS-Ag-SH-HA composite material can ensure the filtration and retention performance of the nanocomposite membrane while also having good antibacterial properties.
[0064] In the antibacterial membranes of Examples 1 to 5, HCNS has a uniform hollow structure and a porous shell layer, which can keenly capture visible light and promote the production of active substances; its huge specific surface area can be Ag + The adsorption and loading of HA-SH provide sufficient and uniform active sites and loading space, allowing it to be dispersed and stably present. Thiolated hyaluronic acid (HA-SH) maintains the biocompatibility and biodegradability of HA itself. On the one hand, the thiol group and silver ion Ag + Chemical reaction occurs to form a stable complex, which is coated on HCNS-Ag + On the other hand, thiolated hyaluronic acid can increase the hydrophilicity of the membrane surface and effectively inhibit the early adhesion of bacteria. When target bacteria appear, the hyaluronidase secreted by the target bacteria will degrade the HA coated on the surface of the HCNS-Ag-SH-HA in the antibacterial membrane, exposing the effective antibacterial component Ag-SH, which can directly contact with microorganisms or slowly release Ag. +To achieve sterilization.
[0065] The above embodiments should not limit the present invention in any way, and any technical solutions obtained by equivalent replacement or equivalent conversion shall fall within the protection scope of the present invention.
Claims
1. An enzyme-responsive visible light nanosilver synergistic antibacterial film, characterized in that: It is prepared by blending HCNS-Ag-SH-HA composite material into membrane material; wherein, the HCNS-Ag-SH-HA composite material is prepared by loading silver ions on hollow carbon nitride spheres and then coating them with thiolated hyaluronic acid compounds; in the antibacterial film, the mass proportion of the HCNS-Ag-SH-HA composite material is 0.1-3%.
2. The enzyme-responsive visible light nanosilver synergistic antibacterial film according to claim 1, characterized in that: The membrane material is one or a combination of two or more of polyethersulfone, polysulfone, polyvinylidene fluoride, cellulose acetate, polyamide and chitosan.
3. A method for preparing an enzyme-responsive visible light nanosilver synergistic antibacterial film as claimed in claim 1 or 2, characterized in that: The specific steps are as follows: A1. Add the HCNS-Ag-SH-HA composite material to an organic solvent and stir until it is evenly dispersed to obtain a mixed solution; A2, adding membrane material to the mixed solution of step A1, heating to dissolve at 50-80°C, stirring for 10-20h, and then standing for 20-30h to remove bubbles to obtain a casting solution; A3, forming an antibacterial film using the casting liquid obtained in step A2.
4. The method for preparing an enzyme-responsive visible light nanosilver synergistic antibacterial film according to claim 3, characterized in that: In step A3, the method of forming the antibacterial film with the casting liquid is as follows: pour the casting liquid of step A2 on the non-woven fabric, spread it evenly, and then immerse the entire non-woven fabric in a gel bath to solidify it to form a film of uniform thickness, and continue immersing it for 24 hours to complete the phase conversion.
5. The method for preparing an enzyme-responsive visible light nanosilver synergistic antibacterial film according to claim 4, characterized in that: In the method for forming an antibacterial film with a casting liquid, the gel bath is pure water, a propanol solution with a volume concentration of 5-10%, or an ethanol solution with a volume concentration of 2-10%.
6. The method for preparing an enzyme-responsive visible light nanosilver synergistic antibacterial film according to claim 3, characterized in that: The HCNS-Ag-SH-HA composite material is prepared according to the following steps: B1, dispersing hollow carbon nitride spheres in water, adding AgNO3 solution thereto, and adjusting the pH of the system to 4-6 with nitric acid; stirring for 10-20 hours in the dark, and then separating the solid, washing, to obtain hollow carbon nitride spheres loaded with silver ions; wherein the mass ratio of the hollow carbon nitride spheres to AgNO3 is 1:(0.34-0.85); B2. The silver ion-loaded carbon nitride hollow spheres prepared in step B1 are dispersed in water, and a thiolated hyaluronic acid compound is added thereto. The mixture is stirred for 8-12 hours at room temperature in the dark, and then the solid is separated. After dialysis and freeze-drying, a HCNS-Ag-SH-HA composite material is obtained. The mass ratio of the silver ion-loaded carbon nitride hollow spheres to the thiolated hyaluronic acid compound is 1:(2-5).
7. The method for preparing an enzyme-responsive visible light nanosilver synergistic antibacterial film according to claim 6, characterized in that: The dispersion in step B1 is ultrasonic dispersion.
8. The method for preparing an enzyme-responsive visible light nanosilver synergistic antibacterial film according to claim 3, characterized in that: The hollow carbon nitride spheres are prepared according to the following steps: C1. Preparation of silica template with core / shell structure; C2, taking the silica template from step C1, acidifying it with HCl solution, separating the solid, and drying it; C3, mixing the solid of step C2 with cyanamide, ultrasonically treating at 65° C. for 4 h, and then stirring at 65° C. for 10-20 h; separating the solid, and then calcining at 550° C. for 4 h in a nitrogen atmosphere, cooling, treating the carbon nitride spheres with ammonium bifluoride solution for 12 h, separating the solid, washing, and freeze-drying to obtain hollow carbon nitride spheres; wherein the mass ratio of the silica template to the cyanamide is 1:(3-7).
9. The method for preparing an enzyme-responsive visible light nanosilver synergistic antibacterial film according to claim 8, characterized in that: The core / shell structured silica template is prepared according to the following steps: D1. Take ethanol, ultrapure water and ammonia water and mix them evenly to obtain a mixed solution; wherein the mass percentage of ammonia water is 25%, and the volume ratio of ethanol, ultrapure water and ammonia water is (12-18):(2-4):1; D2, taking the mixed solution of step D1, adding tetraethyl orthosilicate thereto, stirring evenly, and then standing for 2 hours to obtain a mixed solution containing silica core nanoparticles, wherein the volume ratio of ammonia water to tetraethyl orthosilicate added in step D2 is (1.5-1.8):1; D3, to the mixed solution obtained in step D2, add tetraethyl orthosilicate and octadecyltrimethylsiloxane, stir evenly, then let stand for 10 hours, separate the mixture, and dry; then calcine at 550° C. for 6 hours under air atmosphere to obtain a silica template with a core / shell structure; wherein the volume ratio of tetraethyl orthosilicate added in step D3 to the mixed solution obtained in D2 is (0.025-0.035):1; the mass ratio of tetraethyl orthosilicate added in step D3 to octadecyltrimethylsiloxane is 1:(0.3-0.4).
